Post-progression outcomes of NSCLC patients with PD-L1 expression ≥ 50% receiving first-line single-agent pembrolizumab in a large multicentre real-world study. (May 2021) - Cortellini, Alessio; Cannita, Katia; Tiseo, Marcello; Cortinovis, Diego L.; Aerts, Joachim G.J.V.; Baldessari, Cinzia; Giusti, Raffaele; Ferrara, Miriam G.; D'Argento, Ettore; Grossi, Francesco; Guida, Annalisa; Berardi, Rossana; et al.
Abstract: Background: Treatment sequencing with first-line immunotherapy, followed by second-line chemotherapy, is still a viable option for NSCLC patients with PD-L1 expression ≥50%. Methods: We evaluated post-progression treatment pathways in a large real-world cohort of metastatic NSCLC patients with PD-L1 expression ≥ 50% treated with first-line pembrolizumab monotherapy. Results: Overall, 974 patients were included. With a median follow-up of 22.7 months (95%CI: 21.6–38.2), the median overall survival (OS) of the entire population was 15.8 months (95%CI: 13.5–17.5; 548 events). At the data cutoff, among the 678 patients who experienced disease progression, 379 (55.9%) had not received any further treatment, and 359 patients (52.9%) had died. Patients who did not receive post-progression therapies were older (p = 0.0011), with a worse ECOG-PS (p < 0.0001) and were on corticosteroids prior to pembrolizumab (p = 0.0024). At disease progression, 198 patients (29.2%) received a switched approach and 101 (14.9%) received pembrolizumab ByPD either alone (64 [9.4%]) or in combination with local ablative treatments (37 [5.5%]) (LATs). After a random-case control matching according to ECOG-PS, CNS metastases, bone metastases, and (previous) best response to pembrolizumab, patients receiving pembrolizumab ByPD plus LATs were confirmed to have a significantly longer post-progression OS compared to patients receiving pembrolizumab ByPD alone 13.9 months versus 7.8 months (p = 0.0179) 241 patients (35.5%) among the 678 who had experienced PD, received a second-line systemic treatment (regardless of previous treatment beyond PD). As compared to first-line treatment commencement, patients' features at the moment of second-line initiation showed a significantly higher proportion of patients aged under 70 years (p = 0.0244), with a poorer ECOG-PS (p < 0.0001) and having CNS (p = 0.0001), bone (p = 0.0266) and liver metastases (p = 0.0148). Conclusions: In the real-world scenario NSCLC patients with PD-L1 expression ≥50% treated with first-line single-agent pembrolizumab achieve worse outcomes as compared to the Keynote-024 trial. Poor post-progression outcomes are major determinants of the global results that should be considered when counselling patients for first-line treatment choices. Highlights: Treatment sequencing is a viable option for NSCLC with a PD-L1 expression ≥ 50%. Post-progression pathways of a cohort of NSCLC receiving pembrolizumab were reported. Post-progression outcomes are major determinants for worse clinical outcomes. Our results should be considered when counselling patients for first-line choices.